Hewing to experience : essays and reviews on recent American poetry and poetics, nature and culture - Paul, Sherman (UPCC book collections on Project MUSE., 1989)
". . . The celebration of a point of view that Paul is uniquely equipped to communicate. ... It provides an excellent treatment of the development and practice of a powerful poetic force in modern poetry today, showing the theoretic coherence of Emerson, Whitman, Pound, Williams, and particularly, Olson, as originators and practitioners of 'open' forms."--Thomas Merrill"This book is going to be of value to a number of different readers. For teachers and writers it is a resource and a stimulus for participating in an open poetics. On a utilitarian level it will help to respond to the recent.